The Mediating Role of a Xu-Argument Based Iterative Translation Continuation Task in the Dynamic Relationships Between Translation Learning Anxiety and Foreign Language Learning Proficiency and Translation Strategies - Zhang, Sumin; Ren, Yuhong (Frontiers in Psychology, 2022)
Growing interest has been shown in the effects of the xu-argument based translation continuation task, which have been mainly explored via the linguistic dimension. The current study, using a pretest-intervention-posttest design, investigated the dynamic relationships among translation learning anxiety, foreign language learning anxiety and English-Chinese translation strategies under an iterative translation continuation task that lasted 13 turns. The results yielded from 134 student translators showed a significant increase in their translation strategies comprehension and production, with those with a medium level of translation learning anxiety and foreign language learning proficiency achieving the most. It also showed that the significant partial mediating effect of translation learning anxiety between foreign language learning proficiency and the production of translation strategies in the pre-test became insignificant in the post-test, and the insignificant correlation between the comprehension and production of translation strategies in the pre-test became significant in the post-test. The dynamic relationships among translation learning anxiety, foreign language learning proficiency and translation strategies confirmed the mediating role of the ITCT in attenuating the impact of higher level of translation learning anxiety and lower level of foreign language learning proficiency on the use and comprehension of translation strategies, though its effects could be different for student translators with different levels of translation anxiety and proficiency as measured by different assessments.